Topics and issues of musical education in the news - Violeta HEMSY DE GAINZA (Ediciones Universidad de Salamanca, 2010)
In music education, practice is essential. The new generations of music educators are beginning to understand that while there are many different ways of thinking about music education, is imperative to warn about the polarization of educational thought that exists below the variety of «products» that flow between the two major trends. On these «Notes» some conjectures and arguments may be found, yet global in nature, about the negative influence of political factor in education: the profusion of cognitive «models» and limited number of counter-models aimed at recovering the practical essence of music and music education.